Lessons from Our Sweetgrass Baskets: A Wholistic Vision of Academic Success for Indigenous Women in Higher Education - Brant, Jennifer (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2022)
This qualitative inquiry documents the lessons gleaned from my journey toward the praxis of Indigenous Maternal Pedagogies, an Indigenous women-centred teaching and learning engagement, to offer insights for supporting Indigenous women in higher education. Specifically, this article offers an express vision for Indigenous women’s educational access and success in higher education by sharing a collective research story offered by Indigenous women participants who completed one or more of three courses related to Indigenous women’s literatures and Indigenous maternal theory. Each course was delivered through a decolonial feminist lens, comprised of Indigenous curricular content and engaged students in culturally relevant assessment. This work connects Maternal Pedagogies with Indigenous epistemologies that embrace the “whole student” within educational contexts to establish a teaching and learning environment that can speak to the hearts and minds of students. In the spirit of reconciliation, I position this environment as a safe space where students can be their whole authentic selves and where their realities and lived experiences are positioned as strengths and key assets to establishing an ethical space for cross-cultural and anti-racist dialogue. Collectively, the participant narratives offer four key lessons that are integral to reconciliation education more broadly, and I map these lessons as final recommendations that align with Kirkness and Barnhardt’s timeless work on the “Four Rs” of respect, relevance, reciprocity, and responsibility.